2021
DOI: 10.1101/2021.11.10.21266194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NEMoE: A nutrition aware regularized mixture of experts model addressing diet-cohort heterogeneity of gut microbiota in Parkinson’s disease

Abstract: The microbiome plays a fundamental role in human health and diet is one of the strongest modulators of the gut microbiome. However, interactions between microbiota and host health are complex and diverse. Understanding the interplay between diet, the microbiome and health state could enable the design of personalized intervention strategies and improve the health and wellbeing of affected individuals. A common approach to this is to divide the study population into smaller cohorts based on dietary preferences … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…These inferences require validation in a larger PD GM study and/or meta-analysis. The approach of using the global microbiome signature paired with important clinical measures to identify disease has been developed into a methodological approach pairing nutritional intake with gut enterotypes to define health state ( Xu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…These inferences require validation in a larger PD GM study and/or meta-analysis. The approach of using the global microbiome signature paired with important clinical measures to identify disease has been developed into a methodological approach pairing nutritional intake with gut enterotypes to define health state ( Xu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This was further supported by the newly developed two-stage model, which showed that the incorporation of nutritional data, specifically protein contribution to total energy intake, was able to stratify the cohort into a subpopulation where the association between GM and PD progression was improved. The interpretability of why certain nutritional markers assist in characterizing disease progression is poorly understood and warrants further study ( Xu et al, 2021 ). The recognized preference for increased carbohydrate intake in PD ( Palavra et al, 2021 ) may lead to potential restrictive consumption of protein and its inadvertent contribution to total energy, which could also be further influenced by patient preference to minimize potential levodopa malabsorption, particularly with higher and frequent regiments of levodopa in more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“… 60 https://cran.r-project.org/web/packages/glmnet/index.html NEMoE Xu et al. 33 https://github.com/SydneyBioX/NEMoE poLCA Linzer et al. 63 https://cran.r-project.org/web/packages/poLCA/index.html rsubgroup Atzmueller et al.…”
Section: Methodsmentioning
confidence: 99%
“…rMoE was performed using the implementation from the NEMoE package. 33 rMoE comprises a mixture of experts model 66 with added elastic-net penalties to both the gating and experts networks. Clinical variables were used in the gating network and the metabolite ratios were used in the experts network with the penalty regulariser values of 0.08 and 0.012 respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation